2019
DOI: 10.1111/cge.13509
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified set of obesity‐related genotypes and abdominal fat influence the risk of insulin resistance in a Korean population

Abstract: We aimed to identify obesity‐related single‐nucleotide polymorphism (SNP) loci in a Korean population and construct an obesity genetic risk score (GRS) to examine the association of the genetic predisposition to obesity with insulin resistance (IR). In total, 9675 subjects were included, and 7666 of these subjects were used for replication. A GRS was constructed using the SNP loci that overlapped in both cohort sets. The subjects showed a trend toward an increase in body mass index, waist circumference, systol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…Previous human studies on FARP1 and fatty liver suggested that FARP1 rs9584805 might be related to NAFLD pathology 36 . Another study has demonstrated that other SNPs in FARP1, like rs2127779, were associated with obesity in the Korean population 37 . Our data suggest strong support regarding the role of FARP1 in the pathophysiology of NAFLD, which might be mediated by the effects of rs9584805 on liver fat.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Previous human studies on FARP1 and fatty liver suggested that FARP1 rs9584805 might be related to NAFLD pathology 36 . Another study has demonstrated that other SNPs in FARP1, like rs2127779, were associated with obesity in the Korean population 37 . Our data suggest strong support regarding the role of FARP1 in the pathophysiology of NAFLD, which might be mediated by the effects of rs9584805 on liver fat.…”
Section: Discussionsupporting
confidence: 69%
“…36 Another study has demonstrated that other SNPs in FARP1, like rs2127779, were associated with obesity in the Korean population. 37 Our data suggest strong support regarding the role of FARP1 in the pathophysiology of NAFLD, which might be mediated by the effects of rs9584805 on liver fat. Although the Causal Inference Test 38 did not robustly support the causal role of DNA methylation as a mediator between genotype and outcome (IHF%) in our sample set, methylation-genetic variation cross talk should be considered, 39 by, eg, transcription factors binding to gene target promoters gated by promoter methylation.…”
Section: Discussionsupporting
confidence: 61%
“…Kim et al [58] reported that a 20-SNP obesity GRS showed a significantly greater effect on fasting insulin concentration for men with waist circumferences ≥90 cm and women with waist circumferences ≥85 cm (β = 0.037 ± 0.03) than in less centrally obese subjects (β = 0.003 ± 0.016, p interaction < 0.001). The corresponding effect sizes for HOMA-IR were β = 0.044 ± 0.027 in the wider-waisted participants versus β = 0.001 ± 0.015 in the narrowerwaisted participants (p interaction < 0.001).…”
Section: Adipositymentioning
confidence: 99%